Kuliah Kerja Nyata (KKN) Hutan Kemasyarakatan (HKm) Ekowisata di Desa Kurau Kecamatan Koba Kabupaten Bangka Tengah - Ari Agung Nugroho (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2014)
The Hutan Kemasyarakatan (HKm) Kuliah Kerja Nyata (KKN) Program Ecotourism in Kurau Village is needed to provide a correct understanding to all stakeholders, especially the community, in the midst of mining which is considered an important economic driver number 2 after agriculture. A correct understanding will encourage the formation of HKm groups and will ultimately function HKm groups for the economic welfare of communities in forest areas, and the realization of sustainable forest management. The implementation of the HKm program in the Bangka Belitung Islands Province requires the participation of all parties, both from the community, local government, social agencies, companies and also the academic world. KKN-Thematic is a vehicle for involving the academic community to participate in forest management in the province. KKN-Thematic provides an easy way for campus participation and it is hoped that with real examples that are deeply felt by the community in the Bangka Belitung Islands Province, so that students are honed to care for the development of their region, care for the community and therefore increase social care for the personal development of students.